Unusual case of traumatic carotid artery dissection occurred during a work-related activity. A case report - Garberi, Cesare; Ravizza, Rossana; Colombo, Riccardo; Borromeo, Federica; Rossetti, Chiara; Cisini, Simone; Motta, Marco; Birkhoff, Jutta Maria (La Medicina del Lavoro, 2018)
Carotid artery dissection secondary to cervical blunt trauma is a rare and potentially life-threatening condition that can cause a variety of clinical presentations, including stroke, headache, neck pain, tinnitus, Horner syndrome and cranial neuropathies and is associated with long-term sequelae. We report a case of a 49-year-old industrial vehicles mechanic who was projected to the ground by the explosion of the tire of a heavy truck he was inflating. In the following hours he presented various neurological signs and symptoms and was admitted to the Emergency Department. During hospitalization the patient underwent clinical and instrumental investigations with AngioCT and MR finding of left internal carotid artery dissection in correspondence of its cervical segment and three acute ischemic lesions in the left temporal, parietal and occipital lobes. Medical management was successful and the patient was discharged from the hospital three weeks after the admission but he wasn't able to get back to work due to neurological sequelae. This case report illustrates that traumatic carotid artery dissection, although rare, should be considered in patients who present neurological symptoms after an explosion, can meet the criteria for a work-related injury and may lead to a permanent decrease in the ability to work.